Identification of a Set of Patient-Related Features to Foster Safe Prescribing of Specific Antipsychotics in the Elderly With Dementia - Aguiar, João Pedro; Bernardo, Catarina; Gama Marques, João; Leufkens, Hubert; Alves da Costa, Filipa (Frontiers in Psychiatry, 2020)
The aims of this study were to compile and validate a set of patient-related features (PRFs) to foster safe prescribing of specific antipsychotics (APs) in the elderly with dementia; and to evaluate the feasibility of using them in clinical practice by analyzing the exhaustiveness of medical records. A mixed-methods approach was used, combining a rapid literature review, a two-round e-Delphi survey, and a cross-sectional study in a Portuguese psychiatric hospital. PRFs were identified through a literature search in PubMed (since marketing authorization until October 2019) combined with information from the Summary of Product Characteristics (SmPCs). A total of 450 participants from the e-Delphi were invited by e-mail and included prescribers and eventually specialists in the benefit-risk assessment. During the cross-sectional study, 100 patients were randomly extracted from the hospital database if they were aged 65 or older, diagnosed with dementia, and were prescribed an AP. Outcomes were defined as the assessment of the clinical relevance and feasibility of the PRFs, and the level of exhaustiveness of these features in medical records. Data analysis was performed using univariate statistics (IBM SPSS v.23.0). A total of 92 experts participated in the e-Delphi. Forty-seven PRFs obtained consensus, where 12 were applicable to haloperidol, 14 to olanzapine/risperidone, 13 to quetiapine, and 8 to aripiprazole. Age, comorbidities, and co-medications were rated as important features regardless of the prescribed drug. All PRFs were rated as always or frequently available and, if not, they were easy or partially easy to obtain. Age, comorbidities, and co-medications were always available in the medical records, whereas cognitive status (between 41.4 to 78.8%) or hepatic function (between 17.2 to 30.4%) presented a low-level of exhaustiveness. Even though a high number of PRFs were rated as clinically relevant, some of them were identified as frequently missing from medical records.